Pm10 emission inventory of industrial and road transport vehicles in Klang Valley, Peninsular Malaysia - Jamalani, Mohd Asrul; Abdullah, Ahmad Makmom; Azid, Azman; Ramli, Mohammad Firuz; Baharudin, Mohd Rafee; Chng, Loi Kok; Elhadi Elawad, Rasheida Elawad; Ku Yusof, Ku Mohd Kalkausar; Gnadimzadeh, Azadeh (Faculty of Science and Technology, University of El Oued, 2018)
Rapid development in industrial and road transportation sector in developing countries has contributing the environmental issue. Determining the estimated PM10 emission in Klang Valley, Malaysia is based on the best available resources. Emission of PM10 from both sources was estimated particularly from numbers of industries (industrial area and emission factor) and the usage of motor vehicles (traffic volume, vehicle kilometer travel and emission factor). The PM10 emission from both industrial and road transportation sector were 88.59 tonne PM10/year and 32.36 tonne PM10/year respectively.